2009
DOI: 10.1021/cm900313s
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-to-Blue Upconversion in Colloidal BaYF5:Tm3+, Yb3+ Nanocrystals

Abstract: Tetragonal barium yttrium fluoride (BaYF 5 ) nanocrystals doped with 0.5 mol % Tm 3+ and 15 mol % Yb 3+ (BaYF 5 :Tm 3+ , Yb 3+ ) were synthesized using the thermal decomposition method yielding rectangularshaped nanocrystals (15 nm × 5 nm) that can (up)convert near-infrared light to higher energies such as blue, via a process known as upconversion. The upconversion spectrum of the BaYF 5 :Tm 3+ , Yb 3+ nanocrystals, following excitation with 980 nm, revealed that the upconverted blue emission from the 1 G 4 f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
127
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(135 citation statements)
references
References 28 publications
5
127
1
2
Order By: Relevance
“…A procedure for the sample synthesis is typically described as follows: 0. 25 is polytungstate species). A well-controlled amount of NaOH solution was then added with magnetic stirring to pH 9 to form a little white precipitate (white precipitate is monotungstate species) [30,31].…”
Section: Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…A procedure for the sample synthesis is typically described as follows: 0. 25 is polytungstate species). A well-controlled amount of NaOH solution was then added with magnetic stirring to pH 9 to form a little white precipitate (white precipitate is monotungstate species) [30,31].…”
Section: Preparationmentioning
confidence: 99%
“…At present, AWO 4 were reported to be efficient luminescent hosts for rare earth [20][21][22][23]. Tm 3+ ion is widely used as activator of blue emission corresponding to its 1 D 2 → 3 F 4 and 1 G 4 → 3 H 6 transitions [24][25][26][27][28][29]. Their luminescence spectra consist of several very narrow bands, which make them effective luminescent centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a well known behavior commonly found for realistic upconversion systems under large pump absorption. 23 A saturation behavior has also been found for other upconverting fluoride 4 hosts. The knowledge of the power density value for which saturation begins is of valuable importance for practical applications.…”
Section: à2mentioning
confidence: 66%
“…Owing to their abundant ladder-like energy levels, trivalent lanthanide ions, such as Er 3þ , Tm 3þ , Eu 3þ , and Pr 3þ , have been extensively studied as activator ions for UC processes. 5 Up to now, several trivalent lanthanide-doped UC materials have demonstrated that the tuning of UC multicolor can cover the whole visible light region by adjusting relative intensity of three primary colors red-green-blue (RGB). 6 In particular, by precise control of the combination and concentration of Ln 3þ ions, one may obtain efficient and singlephased white-light emitting phosphors.…”
Section: Introductionmentioning
confidence: 99%